Study on Relationship Between Hormones and Aggression In Different Animals and Human: Exploring the Link Between Hormones and Aggressive Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Although it seems that everybody understands whataggression is, yet there is considerable disagreement about how to define it.The published literature on human aggression show variations in definitionsproposed. From the review of literature related to the conceptualization ofhuman aggression, it is clear that three important distinctions should be madefor proper understanding of the concept. The first is whether it should bedefined simply interms of hurtful behaviour, or a persons hurtful intentionsshould be taken into consideration. Behaviourists have taken aggression as anybehaviour that hurts others. The advantage of this definition is that thebehaviour itself determines whether or not an act is aggressive. But thisdefinition ignores the intention of person who does this act. Intentions have acentral role in the judgments about aggression. In this context aggression canbe taken as any action that is intended to hurt others.